An in vitro evaluation of microhardness of different direct resin-based restorative materials on using 10% carbamide peroxide gel as a bleaching agent - Raji Viola Solomon; Chaitanya Byragoni; Ashish Jain; Yogendher Juvvadi; Ravindra Babu (Wolters Kluwer Medknow Publications, 2016)
Purpose: This in vitro study was done to evaluate the effect of a 10% carbamide peroxide bleaching agent on the micro hardness of three types of direct resin-based restorative materials. Materials and Methods: Fifteen disk-shaped specimens (5.0 mm diameter and 2.0 mm depth) of each material, including a micro hybrid resin composite (Z250), a nanofilled resin composite (Z350), a hybrid resin composite (Z100), were fabricated and then polished with medium, fine, and superfine polishing discs. After being polished, specimens were cleaned with distilled water for 2 min in an ultrasonic bath to remove any surface debris and then stored in distilled water at 37ΊC for 24 hours. Specimens from each material were divided into three groups (n=5). One group was selected as a control group (non treated with bleaching agent). The other two groups were treated with bleaching agent for 14 days (group A) and followed by immersion in artificial saliva for 14 days (group B). The top surfaces of the specimens in the different groups were also subjected to the Vickers hardness test with a load of 300 g and 15-second dwell time. Data were analyzed witha one-way analysis of variance and Turkey's HSD test (α = 0.05). Results: There was a general reduction of Vickers hardness numbers (VHN) values of treated groups compared with the control group for each material used, but this reduction was minimal, with no significant difference between groups in Z250, whereas the other two materials (Z350, Z100) showed a significant reduction of VHN of treated groups compared with the control group. Conversely, the findings showed no significant difference between treated groups A and B in all materials used. Conclusion: A 10% carbamide peroxide bleaching agent had an adverse effect on the micro hardness of nanofilled and hybrid types of resin-based composite materials compared with the micro hybrid type.